Effects of compaction and suction on the hydromechanical properties of a dam core clay. (March 2021) - Lachgueur, Karima; Abou-Bekr, Nabil; Taibi, Said; Fleureau, Jean-Marie
Highlights: Effects of compaction energy and suction on mechanical behavior of dam core soil. Contours of equal suction are analyzed along compaction curves. Density and suction are compared on drying-wetting paths and along compaction curve. Elastic modulus is analyzed along compaction curves. Bearing capacity is studied along compaction curve at different energies. Abstract: The paper presents an experimental study of the hydromechanical behavior of a compacted clay used in the design of the core of the Boughrara dam (western Algeria). The influence of compaction energy level (CEL) is explored using three different energies: Standard Proctor energy (SP), reduced Proctor energy (SP-20 blows) and enhanced Proctor energy (SP+ 20 blows). The resulting compaction curves are supplemented by measurements of suction, which is a very important parameter in the behavior of compacted unsaturated soils. In addition to the compaction curves, elastic modulus and immediate bearing capacity ratio (IBCR ) are measured, and related to suction and compaction energy level (CEL). Mechanical compaction paths following the SP curve and drying-wetting paths starting from SPO are compared. Mechanical properties such as E-modulus and IBCR are related to the two independent major parameters γd and Sr . Measuring these mechanical properties in the field allows to evaluate the compaction state regardless of the CEL. The results are compared with those of the literature.